CIPP EVALUATION MODEL IN LEARNING IN MADRASAH IBTIDAIYAH - Rahmayanti, Jesica Dwi; Chusnah, Nuning Isfa' Nisaul; Suparto, Suparto (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2024)
This research aims to describe the CIPP evaluation model at Madrasah Ibtidaiyah. The research uses a type of library research with a content analysis method to explore data that has been collected through the Google Scholar database and books in online libraries related to the topic being studied. The research results show that the CIPP evaluation model is carried out comprehensively to understand the activities of a particular program, starting from the emergence of the idea to the results obtained from the program created. The basic concept of the CIPP model is to evaluate several components including context, input, process and product. The CIPP model has several objectives including context evaluation to serve planning decisions, input evaluation, structuring decisions, process evaluation, to serve implementing decisions, product evaluation, to serve recycling decisions. Compared to other evaluation models, the CIPP model has several advantages, namely being more comprehensive, having a holistic approach, having the potential to move in the area of formative and summative evaluation, being able to provide a good basis for making decisions and policies as well as preparing further programs. However, apart from these advantages, of course there are also disadvantages. The shortcomings of the CIPP evaluation model are that it is too concerned with where the process should be rather than the reality in the field, tends to focus on rational management, application in the field of classroom learning has a low level of implementation.